Genetic diversity and population structure of Brycon nattereri (Characiformes: Bryconidae): a Neotropical fish under threat of extinction - Galindo,Bruno A. (2019)
ABSTRACT Brycon nattereri is an endangered Neotropical fish reported along conserved stretches of the upper Paraná, Tocantins and São Francisco rivers. Populations of this species have been very rare in some Paraná River sub basins. This study analyzes the genetic diversity and population structure of B. nattereri in a restricted area of occurrence recently identified in upper Paraná River basin. Seven microsatellite loci and 497 bp of D-Loop mitochondrial region were examined in 92 individuals from four points along the area of occurrence. Both molecular markers indicated a single population distributed along a stretch of the river approximately 80 km long. Although some of the data suggest an ancient bottleneck, current levels of genetic diversity (H E = 0.574 and h = 0.616) were similar to those of other species of the genus Brycon. The results suggest that the population of B. nattereri has been able to maintain satisfactory levels of genetic diversity, in spite of the small area of occurrence. These data have highlighted an important conservation area and action may prove essential to improve the quality of the environment, and especially the water and riparian plant life, if the area is to be managed and conserved efficiently.